Efficient Ternary Organic Solar Cells Enabled by the Integration of Nonfullerene and Fullerene Acceptors with a Broad Composition Tolerance. (6th December 2018) - Fu, Huiting; Li, Chao; Bi, Pengqing; Hao, Xiaotao; Liu, Feng; Li, Yan; Wang, Zhaohui; Sun, Yanming
Abstract: The ternary structure that combines fullerene and nonfullerene acceptors in a photoactive layer is demonstrated as an effective approach for boosting the power conversion efficiencies (PCEs) of organic solar cells (OSCs). Here, highly efficient ternary OSCs comprising a wide‐bandgap polymer donor (PBT1‐C), a narrow‐bandgap nonfullerene acceptor (IT‐2F), and a typical fullerene derivative (PC71 BM) are reported. It is found that the addition of PC71 BM into the PBT1‐C:IT‐2F blend not only increases the device efficiency up to 12.2%, but also improves the ambient stability of the OSCs. Detailed investigations indicate that the improvement in photovoltaic performance benefits from synergistic effects of increased photon‐harvesting, enhanced charge separation and transport, suppressed trap‐assisted recombination, and optimized film morphology. Moreover, it is noticed that such a ternary system exhibits excellent tolerance to the PC71 BM component, for which PCEs over 11.2% can be maintained throughout the whole blend ratios, higher than that (11.0%) of PBT1‐C:IT‐2F binary reference device. Abstract : Ternary organic solar cells with improved power conversion efficiency (PCE) and ambient stability are developed by combining a nonfullerene acceptor and a fullerene acceptor. Such a ternary system is insensitive to the content of the third component, and PCEs over 11.2% can be maintained throughout the whole blend ratios, higher than that (11.0%) of the binary reference device.